Evaluation of extracts of Borassus flabellifer dust as green inhibitors for aluminium corrosion in acidic media. (December 2019) - Nathiya, R.S.; Perumal, Suresh; Murugesan, Vajjiravel; Raj, V.
Abstract: In this paper, corrosion inhibition ability of Borassus flabellifer coir dust thus extracted by water (BFDWE) and methanol (BFDME) against aluminum in 1 M H2 SO4 at 303–333 K has been examined using electrochemical, non-electrochemical, and microstructural analysis. The experimental results depicted that corrosion inhibition efficiency increases with addition of inhibitor content and it adversely decreases as a function of temperature. Particularly, the highest inhibition efficiencies of 66.8 %and 52% were achieved for the extracts of BFDME and BFDWE, respectively, for inhibitor concentration of 0.4 g/l. Further, adsorption of molecules, presence in BFDME and BFDWE, on active sites of aluminum surface was of physisorption and it obeyed Langmuir adsorption isotherm. Potentiodynamic polarization results showed that BFDME and BFDWE perform as mixed-type inhibitors with notable cathodic nature. The surface morphological study by scanning electron microscope (SEM) further confirmed the existence of passive layers of BFDME and BFDWE molecules on top of aluminum's surface and thus promotes anti-corrosion.